Effects of Exenatide and Lifestyle Modification on Body Weight and Glucose Tolerance in Obese Subjects With and Without Pre-Diabetes - Rosenstock, Julio (American Diabetes Association, 2010)
OBJECTIVE: To assess the effects of exenatide on body weight and glucose tolerance in nondiabetic obese subjects with normal or impaired glucose tolerance (IGT) or impaired fasting glucose (IFG). RESEARCH DESIGN AND METHODS: Obese subjects (n = 152; age 46 ± 12 years, female 82%, weight 108.6 ± 23.0 kg, BMI 39.6 ± 7.0 kg/m(2), IGT or IFG 25%) were randomized to receive exenatide (n = 73) or placebo (n = 79), along with lifestyle intervention, for 24 weeks. RESULTS: Exenatide-treated subjects lost 5.1 ± 0.5 kg from baseline versus 1.6 ± 0.5 kg with placebo (exenatide − placebo, P < 0.001). Placebo-subtracted difference in percent weight reduction was −3.3 ± 0.5% (P < 0.001). Both groups reduced their daily calorie intake (exenatide, −449 cal; placebo, −387 cal). IGT or IFG normalized at end point in 77 and 56% of exenatide and placebo subjects, respectively. CONCLUSIONS: Exenatide plus lifestyle modification decreased caloric intake and resulted in weight loss in nondiabetic obesity with improved glucose tolerance in subjects with IGT and IFG.